Source attribution of human echinococcosis: A systematic review and meta-analysis - Torgerson, Paul R.; Robertson, Lucy J.; Enemark, Heidi L.; Foehr, Junwei; van der Giessen, Joke W. B.; Kapel, Christian M. O.; Klun, Ivana; Trevisan, Chiara (PLOS Neglected Tropical Diseases, 2020)
Author summary Echinococcus granulosus and E. multilocularis are zoonotic parasites that cause human cystic (CE) and alveolar (AE) echinococcosis, respectively: both diseases resulting in a substantial burden of disease. They are transmitted to humans via wild or domestic caniid definitive hosts. This study aimed at finding and evaluating the source attribution of echinococcosis and provides evidence that transmission by direct contact with the definitive hosts perhaps results in 26.1% and 34.4% cases of CE and AE, respectively. Indirect transmission by contaminated water may result in 29.4% and 24.8% of cases of CE and AE, respectively. There is evidence that indirect transmission through contaminated food may result in 23.4% of cases of CE globally. Contaminated food may result in 32.5% of cases of AE, but only in low incidence regions such as Europe. In areas of high human incidence such as China, the evidence for foodborne AE was not convincing. Other sources of transmission such as contact with a contaminated environment result in approximately 21.1% of CE cases and 11.1% of AE cases.